The Fate of Phosphate: Assessing Dietary Intake and Urinary Excretion in Swedish Adolescents - Fredrik Söderlund; Jennifer Gransten; Emma Patterson; Anna Karin Lindroos; Sanna Lignell; Carolina Donat-Vargas; Linnea Bärebring; Susanna C Larsson; Maria Kippler; Agneta Åkesson (Current Developments in Nutrition, 2024)
Background: A high total phosphorus (P) intake has been proposed to promote endothelial dysfunction and atherosclerosis. A diet rich in foods containing P additives could contribute to an excessive intake, potentially reflected as increased concentration of P in urine. Objectives: This study aimed to assess the intake of total dietary P, P additives, and its sources and examine their correlation with urinary P in a cross-sectional national study in Swedish adolescents. Methods: We constructed a database of P additives and applied it to the foods consumed by 3099 participants in the representative school-based dietary survey Riksmaten Adolescents 2016–17. Intake of total dietary P and P additives were assessed using two 24-h recalls. Urinary P was analyzed in a subsample of 756 participants using inductively coupled plasma mass spectrometry. Spearman rank correlation (ρ) was used to assess the association between dietary P intake and urinary P excretion. Results: The mean (SD) intake of total P was 1538 (±667) mg/d. Food containing P additives were consumed by 92% of adolescents and the median (IQR) intake was 49 (22–97; range: 0.01–947) mg/d, corresponding to 5% (1%–6%; range: 0%–50%) of total P. The main contributing food to P additives was cola drinks, while the main contributing food group was sausage dishes. Total P intake was weakly correlated with urinary P (ρ = 0.12; P < 0.01) but not with intake of P additives. Conclusions: Nearly, all participants consumed P additives, contributing to an average of 5% of total P intake but ranging up to 50%. The intake of total P, but not P additives, was weakly reflected in the urinary P. Access to more comprehensive information on P additives in foods would improve further evaluation of potential health consequences.